Public health threat with consumption of unpasteurized milk: Systematic review: Public health threat with consumption of unpasteurized milk - Ali, Mansoor; Ketema, Sisay; Prabakusuma, Adhita Sri; Aslam, Maryum; Durrani, Yasser; Akhtar, Naheed; Fiza Nayab, Syeda; Sajjad, Muhammad; Khalid, Mahreen; Umar, Muhammad; Kanwal, Freeha; Ullah, Ikram (Pakistan Journal of Health Sciences, 2022)
Unpasteurized milk consumption is common throughout the globe, despite the negative consequence for consumer health. This review paper identified public health risks resulting from unpasteurized milk. Several keywords were used to search online, including Google Scholar, PubMed, Science Direct, and academic publications. Significant data were rigorously extracted and reported as per the PRISMA statement guideline. Individuals' risk from consuming raw milk was examined in 15 studies. According to a laboratory investigation report, raw milk contained several parasites and harmful bacteria in unpasteurized milk. These include campylobacteriosis, brucellosis, Staphylococcus aureus, streptococcus, salmonellosis, E. coli 0157, and other hazardous poisons like Aflatoxin M1. People are exposed to pathogenic microorganisms, parasites, and other dangerous toxic agents while consuming raw milk. Therefore, ensuring the safety and quality of raw milk through implementing hazard-critical control points during production and distribution is mandatory in the dairy industry to safeguard general public health.